The contributions of school and classroom climate to mathematics test scores: a three-level analysis. Issue 1 (2nd January 2023) - López, Verónica; Salgado, Mauricio; Berkowitz, Ruth
ABSTRACT: Supportive school and classroom climates can add to student achievement and compensate for the negative contribution of low-socioeconomic status (SES) to academic achievement. We tested the added contribution of school and classroom climate to Chilean students' mathematics test scores. We performed a secondary analysis of 151, 015 eighth-grade students (attending 8, 412 classrooms in 5, 619 schools) who completed the Sistema de Medición de la Calidad de la Educación (SIMCE) test in Chile. We identified six dimensions of school climate, which we aggregated to the classroom and school level to fit three-level regression models. Students' gender (girls) and low SES were major negative predictors of test scores. School and classroom climate made an additional contribution to the explained variance in test scores. A positive school and classroom climate compensates for the detrimental effects of gender and low SES on students' mathematics achievement, which justifies investing resources to promote positive school and classroom climates.